Evaluation of the legal periodical collections of selected law school libraries in Metro Manila a follow-up study - Oblefias, Chantelle M.; Santos, Antonio M. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
One way of improving the field of librarianship and library service is to keep track of the improvement and impacts of previous researches through follow-up studies. Journals are one of the most important publication in any field of knowledge for it serves as a tool for providing up to date findings and developments particularly the dynamic field of law.
This is a follow up study of a thesis entitled Evaluation of Legal Periodical Collection of Selected Law School Libraries in Metro Manila conducted in 1996. The institutions involved were the Ateneo de Manila University Law School Library, San Beda College of Law Library, the University of Santo Tomas Faculty of Civil Law Library and the University of the Philippines College of Law Library.
This study aims to look into the legal periodical collections of the law school libraries from 1996-2004, to determine the subject concentration of each collection and to come up with a Union List. Factors affecting selection and acquisition are also examined.
Findings revealed that most of the law school libraries' legal periodical collection has declined in terms of numbers. Given the advancement in technology, most of the legal periodicals remain to be in its traditional printed form. The subject concentration of the legal periodical collections of the selected law school libraries in Metro Manila has shifted within a period of eight years.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Law libraries -- Philippines -- Manila Metropolitan Area -- Periodicals -- Evaluation